2018
DOI: 10.3748/wjg.v24.i46.5271
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between response to lusutrombopag and splenic volume

Abstract: AIMTo assess the correlation between the efficacy of lusutrombopag and clinical characteristics in patients with chronic liver disease.METHODSIn this retrospective, multicenter study, which conducted at four locations in Japan, 50 thrombocytopenic patients with chronic liver disease were enrolled. All patients received oral lusutrombopag (3.0 mg/d for 7 d) for chronic liver disease. We assessed the increase in platelet count after the trial drug administration. A treatment response was defined as a platelet co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 26 publications
1
22
2
Order By: Relevance
“…Nevertheless, despite the differences in characteristics between patients enrolled in the clinical trials compared with the present surveillance, it is reassuring that the present results confirm the safety and effectiveness of lusutrombopag, and further validate the results of the clinical trials . These interim results are also consistent with other recent reports of the safety and effectiveness of lusutrombopag in both treatment‐naïve and retreatment patients …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nevertheless, despite the differences in characteristics between patients enrolled in the clinical trials compared with the present surveillance, it is reassuring that the present results confirm the safety and effectiveness of lusutrombopag, and further validate the results of the clinical trials . These interim results are also consistent with other recent reports of the safety and effectiveness of lusutrombopag in both treatment‐naïve and retreatment patients …”
Section: Discussionsupporting
confidence: 92%
“…[7][8][9] These interim results are also consistent with other recent reports of the safety and effectiveness of lusutrombopag in both treatmentnaïve and retreatment patients. [14][15][16] Lusutrombopag is currently the only thrombopoietin receptor agonist with available postmarketing surveillance data for treatment of patients with CLD and thrombocytopenia undergoing invasive procedures. Another agent, avatrombopag, was approved in the USA in May 2018, but no real-world surveillance data have yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, a baseline platelet count of < 30 × 10 3 /μL was the only significant factor preventing platelet counts from reaching 50 × 10 3 /μL with lusutrombopag treatment. While it is true that splenomegaly may prevent the improvement of thrombocytopenia as reported by Uojima et al, 9 patients with advanced splenomegaly often experience severe thrombocytopenia from the outset. The level of elevation of platelets is limited.…”
Section: Discussionmentioning
confidence: 89%
“…4 However, patients who undergo transfusions can face certain complications including febrile nonhemolytic allergic reactions or infections. 9 As such, we conducted this study to assess whether splenomegaly is indeed associated with the insufficient improvement of platelet counts after either platelet transfusion or lusutrombopag administration. Recently, however, it was suggested that splenomegaly may prevent the improvement of thrombocytopenia in patients administered with lusutrombopag.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation